Cognitive frailty and the aging gut: long term research grant scheme (LRGS) Ministry of Higher Education (MOHE) - Abdul Majeed, Abu Bakar; Ramasamy, Kalavathy; Lim, Siong Meng (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, UiTM is proud to be part of the Transforming Cognitive Frailty into Later-Life Self-Sufficiency (AGELESS) research program that was funded by the Ministry of Higher Education under the LRGS (2019-2025). The entire AGELESS research programme led by Professor Dr. Tan Maw Pin from the University of Malaya (UM) comprised of 5 key projects and involved 50 coinvestigators from seven universities (public and private) in Malaysia. Professor Dato’ Dr. Abu Bakar Abdul Majeed had the privilege to lead Project 3 which featured “Decoding Phenome to Unravel the Mechanisms of Cognitive Frailty”.